USEFUL TECHNIQUES IN TEACHING VOCABULARY TO GRADE 10 STUDENTS - Vu, Thi Huyen Trang (2020)
The study titled “Useful techniques in teaching vocabulary to grade 10 students” is conducted in the hope that it can help grade 10 students overcome difficulties in mastering, enriching their vocabulary and grade 10 teachers better their vocabulary teaching techniques .The researcher carried out the research using two main instruments : survey questionnaire and oral interviews. A survey was conducted with the contribution of 100 grade 10 students and 8 teachers at Hoan Kiem – Tran Phu upper secondary school in Hanoi. The major findings of the research figured out that mismatching between teaching and learning styles was the greatest problem that caused the ineffectiveness of vocabulary learning at grade 10. Based on students and teacher’s preference towards useful techniques in teaching vocabulary at grade 10, the researcher made suggestions on useful techniques in vocabulary teaching.